2020
DOI: 10.1111/hsc.13205
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and health behaviors as predictors of changes in self‐rated health among older persons in Israel

Abstract: Epstein, 2020), driven by reductions in infant and child mortality and by the decrease in mortality in older people, specifically deaths from non-communicable diseases (Mathers et al., 2015). Increased life expectancy, however, does not necessarily mean that the extra life is spent in good health ("healthy life years"). Thus, most countries conduct regular health surveys to monitor the different aspects of health, among them self-rated health (SRH) (OECD, 2017).SRH is a common measure of health status that has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…We were able to identify five SRH-change categories; stable high, stable moderate, and stable low in addition to a decline category and an improvement category. Previous studies investigating SRH in older adults identified only three change categories (no change, improvement, and decline), with the majority of the participants showing no change in SRH over the follow-up period, which is in agreement with the results of our study when the three stable categories are combined [30][31][32]. Two of the aforementioned studies reported a higher proportion of individuals in the improvement category than in the decline category [30,32].…”
Section: Discussionsupporting
confidence: 92%
“…We were able to identify five SRH-change categories; stable high, stable moderate, and stable low in addition to a decline category and an improvement category. Previous studies investigating SRH in older adults identified only three change categories (no change, improvement, and decline), with the majority of the participants showing no change in SRH over the follow-up period, which is in agreement with the results of our study when the three stable categories are combined [30][31][32]. Two of the aforementioned studies reported a higher proportion of individuals in the improvement category than in the decline category [30,32].…”
Section: Discussionsupporting
confidence: 92%
“…This study draws on data collected by the Survey of Health, Aging and Retirement in Europe (SHARE), which seeks to better understand the dynamics of the growing population of persons aged 50+ and to provide a research infrastructure for public policymaking on behalf of the older-adult population [35]. The data collected in SHARE make it possible to compare the health, economic situation, and welfare of older adults in 29 European countries over time by providing a multidisciplinary cross-national bank of microdata on health, psychological, and economic variables [36][37][38].…”
Section: Data Source and Study Samplementioning
confidence: 99%
“…Notably, Arabs also tend to rate health system responsiveness higher than Jews do, but there are indications that this may be due to lower expectation levels rather than better levels of care in practice [ 35 ]. Furthermore, in the time-dependent analysis that considered changes in SRH between two time points in the Jewish and Arab populations, the results showed that Arab Israelis exhibited a weaker deterioration in SRH compared to Jewish Israelis [ 42 ]. These findings may warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%